HUBUNGAN KEBERSIHAN GIGI DAN MULUT DENGAN TRIMESTER KEHAMILAN PADA IBU HAMIL YANG BERKUNJUNG KE PUSKESMAS KLUNGKUNG I KABUPATEN KLUNGKUNG TAHUN 2016 - I Nyoman Gejir; Ni Kadek Ayu Sukartini (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
Oral health of the pregnant mother affects the condition of the baby it contains. Pregnant women who suffer from periodontal infection are at risk of giving birth to babies with low birth weight and are premature. Early pregnancy usually pregnant women experience lethargy, nausea and sometimes until vomiting. Increased plaque because it is lazy to maintain cleanliness, will accelerate tooth decay. Ni Kadek Ayu Sukartini's research results at the Klungkung I Health Center obtained the average level of dental and oral hygiene in pregnant women in the first, second and third trimester criteria. The purpose of this study was to determine the relationship between dental and oral hygiene with trimester of pregnancy in pregnant women who visited the Klungkung I Health Center in Klungkung Regency in 2016. This type of cross sectional study used secondary data from Ni Kadek Ayu Sukartini's research. Spearman's correlation test. Spearman’s test results obtained sig value: 0.426. Conclusions there is no relationship between the trimester of pregnancy with the oral hygiene of pregnant women who visited the Health Center Klungkung I in 2016.